Recovery of L-lactic acid from fermantaion broth by using strong anionic resin. - Quan, Nguyen Minh; Van, Ngo Thi Thanh (Vietnam Journal of Chemistry, 2012)
The technique of ion exchange for separation of lactic acid from fermentation broth is used in our study. The ion exchange resin used is a strong anionic resin, a product of Jacobi Carbons Company, Italy (trade name is Resinex A-4). The process at laboratory scale is realized in a chromatographic column with dimensions d x h = 10mm x 110mm which contains 6 g of anionic resin. Two solvents used are distilled water and methanol. The HPLC analysis shows a good efficacy of distilled water.